MODEL OF DETERMINANT FACTORS IN IMPROVING PRODUCTIVITY AND SUSTAINABILITY OF POTATO FARMING IN KERINCI DISTRICT (WITH SEM-PARTIAL LEAST SQUARE APPROACH) - Fitri, Yanuar; Fauzia, Gina; Nainggolan, Saidin (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2024)
Potato farming productivity is one indicator of improving the farming business, including its sustainability. Higher farming productivity will be accompanied by increased production. This study aims to analyze the determinants of factors that influence the increase in productivity and sustainability of potato farming. This research was conducted in Kayu Aro Barat District, which was determined purposively. The research locus was Sungai Asam Village, Kebun Baru Village, and GIRI Mulyo Village. The population size of the three villages was 1,100 farmers. Using the Slovin method, a sample size of 76 respondent families was obtained. The sampling method was simple random sampling. The data analysis method used SEM - PLS. The results showed that the description of internal factors, external factors of farmers, and the use of production inputs were in the medium category. The category of productivity and sustainability of potato farming was in the low category. The internal factor that was a determinant of productivity and sustainability of potato farming was the farm income variable. External factors that are determinants of productivity and sustainability of farming are access to credit, access to technology, access to access. This research aims to analyze the impact of internal factors, external factors and technology adoption on productivity and sustainability of potato farming. Meanwhile, the variable of production input use that is a determinant factor of productivity and sustainability of potato farming is land area and fertilizer use. Internal and external factors that need to be considered in modeling increasing productivity and sustainability of potato farming are the use of production inputs by means of assistance with production facilities, working capital assistance and technological assistance. This can be done through policies to increase farmer access to credit, production facilities and potato farming technology.